2019
DOI: 10.1111/odi.13235
|View full text |Cite
|
Sign up to set email alerts
|

DKK1 and TNF‐alpha influence osteogenic differentiation of adBMP9‐infected‐rDFCs

Abstract: Objectives Rat dental follicle cells (rDFCs) function as precursor cells of periodontal tissues. Bone morphogenetic protein (BMP9) plays an important role in proliferation and differentiation. Tumour necrosis factor‐alpha (TNF‐alpha) is an important contributor to bone resorption. Wnt canonical pathway can be inhibited by Dickkopf 1 (DKK1). The aim of the study was to enhance the osteogenesis of BMP9 treated rDFCs in an inflammatory environment and elucidate the mechanism. Materials and Methods rDFCs were infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…the late dental development stage via cellular migration and differentiation (5-7). adBMP9 acts on cells as an exogenous factor to safely and effectively transfect the target gene into the target cell (8)(9)(10)(11)(12)(13). The present study transfected cells with an adenovirus to construct an adBMP9-transduced rdFc model.…”
Section: Tnf-α Regulates the Wnt Signaling Pathway During The Bmp9-inmentioning
confidence: 96%
See 4 more Smart Citations
“…the late dental development stage via cellular migration and differentiation (5-7). adBMP9 acts on cells as an exogenous factor to safely and effectively transfect the target gene into the target cell (8)(9)(10)(11)(12)(13). The present study transfected cells with an adenovirus to construct an adBMP9-transduced rdFc model.…”
Section: Tnf-α Regulates the Wnt Signaling Pathway During The Bmp9-inmentioning
confidence: 96%
“…TnF-α levels were reported to be markedly increased in the gingival crevicular fluid of patients with periodontitis and the expression levels of TnF-α have been closely associated with the severity of periodontitis (29,30). Previous studies have identified that TNF-α suppressed cell osteogenic differentiation (8,21,31,32). it was also discovered that high concentrations of TnF-α suppressed the expression of osteogenesis-related factors, such as alP, ocn and runX2 in mesenchymal stem cells (33,34).…”
Section: Tnf-α Regulates the Wnt Signaling Pathway During The Bmp9-inmentioning
confidence: 99%
See 3 more Smart Citations